Transcatheter aortic valve implantation in an orthotopic heart transplant recipient with bicuspid aortic valve. Issue 11 (17th October 2018) - Akleh, Subhi I.; Bandali, Alykhan; Edwards, Richard
Key Clinical Message: Increasing longevity of heart transplantation recipients and aging donor population accompanied by the older age at transplantation led to an increase in the prevalence of degenerative valvular disease in particular aortic stenosis. TAVI is considered a safe and feasible alternative compared to conventional SAVR in this high‐risk population. Abstract : Increasing longevity of heart transplantation recipients and aging donor population accompanied by the older age at transplantation led to an increase in the prevalence of degenerative valvular disease in particular aortic stenosis. TAVI is considered a safe and feasible alternative compared to conventional SAVR in this high‐risk population.